2022
DOI: 10.1126/scisignal.abl6179
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoids produced in photoreceptor cells in response to light activate Drosophila TRP channels

Abstract: Drosophila phototransduction is a model for signaling cascades that culminate in the activation of transient receptor potential (TRP) cation channels. TRP and TRPL are the canonical TRP (TRPC) channels that are regulated by light stimulation of rhodopsin and engagement of Gα q and phospholipase Cβ (PLC). Lipid metabolite(s) generated downstream of PLC are essential for the activation of the TRPC channels in photoreceptor cells. We sought to identify the key lipids produced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Lipid mediators derived from cell membrane lipids also directly activate TRP channels as was shown for mammalian TRPV activation by endocannabinoids such as 2-AG (2-arachidonoyl glycerol) and N-acylethanolamines ( Sisignano et al, 2014 ). In Drosophila , a recent study showed that 2-LG (2-linoleoyl glycerol), endocannabinoid derived from linoleic acid-containing phospholipids, activate TRP and TRPL, which is involved in visual signaling in the compound eye ( Sokabe et al, 2022 ).…”
Section: Membrane Lipids As Modulators Of Thermosensitive Trp Channelsmentioning
confidence: 99%
“…Lipid mediators derived from cell membrane lipids also directly activate TRP channels as was shown for mammalian TRPV activation by endocannabinoids such as 2-AG (2-arachidonoyl glycerol) and N-acylethanolamines ( Sisignano et al, 2014 ). In Drosophila , a recent study showed that 2-LG (2-linoleoyl glycerol), endocannabinoid derived from linoleic acid-containing phospholipids, activate TRP and TRPL, which is involved in visual signaling in the compound eye ( Sokabe et al, 2022 ).…”
Section: Membrane Lipids As Modulators Of Thermosensitive Trp Channelsmentioning
confidence: 99%
“…The main differences between the seven TRP channel subfamilies are found in the N-and C-terminal cytosolic domains, which contain putative protein inter-action and regulatory motifs [40]. TRP channels are activated in several ways: directly by endogenous agents, including diacylglycerols [41], phosphoinositides [42], eicosanoids [43], anandamide [44], and reactive oxygen species (ROS) and their byproducts [45,46], and by an unprecedented series of exogenous compounds, such as capsaicin [47], icilin [48], allicin [49], allyl isothiocyanate (AITC) [50,51], isopetasin [52], umbellulone [53,54], parthenolide [55], and acrolein [56], or indirectly, by intracellular mediators produced by the activation of G protein-coupled receptor (GPCR) or tyrosine kinases receptor [57].…”
Section: Trp Channelsmentioning
confidence: 99%
“…Isolated photoreceptor cells from drosophila wild type and rdgA (DAG kinase) mutants show constitutive TRP activity. Recently, endocannabinoids produced in Drosophila photoreceptor cells in response to light have been shown to activate TRP channels ( Sokabe et al, 2022 ). In addition, using flies engineered to express genetically encoded ER calcium indicator, the sodium/calcium exchanger has been shown to result in rapid calcium release from the ER upon light exposure ( Liu et al, 2020 ).…”
Section: History Of Socementioning
confidence: 99%